STUDY OF THE ELECTRICAL PROPERTIES OF p-Si SAMPLES - Berkinov Elmurod Khoshimjonovich, Murodullayev Doniyorbek Mirzokhid ugli, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
Currently, the study of the influence of impurity atoms on the electrical properties of semiconductor materials is of particular importance [1-11]. This paper presents the results of studies of the electrical properties of p-Si samples. Single crystalline silicon of the KDB-0.3 grade, grown using the Czochralski method, was used as the initial sample. Diffusion was carried out at temperature T=1473 K for t=1.5 hours.